Adaptation and Testing of an Instrument to Measure Energy Literacy in Mexico - Valerio-Ureña, Gabriel; Castañeda-Garza, Gerardo (Proceedings of the International Conference on Education, 2020)
We live in a continuous dependence to energy, and yet, there does not exist a clear sight about what we know and what we ignore about energy. Energy literacy is a broad term encompassing content knowledge as well as a citizenship understanding of energy that includes affective and behavioral aspects. In this study, of quantitative nature with exploratory scope, the purpose was to create an adaptation, and application of a pilot test, of the questionnaire “Energy Literacy Survey” (DeWaters & Powers, 2009) in a sample of university students from Mexico. The method included a translation procedure, the regional adaptation and the development of the pilot test. The sample consisted in a total of 114 participants. The questionnaire was made of 64 items in three sub-scales (cognitive, affective and behavioral). Being an adaptation from an original instrument, reliability and relevance of the items were evaluated. Factorial analysis was used to evaluate the importance of the items. Affective sub-scale showed values superior to 0.5, suggesting relevance in those items, except for two items (A7 and A8). Behavior sub-scale reports as well most of its values superior to 0.5, with exception of items B4 and B10. In terms of reliability, Cronbach’s alpha was calculated. The affective sub-scale obtained 0.581, being able to increase its value to 0.652 if A5 was removed. On the other hand, behavior sub-scale obtained 0.691, being able to increase to 0.710 if one item was removed. Results of the pilot show differences between students of the faculties of science, engineering and others, as well as differences by gender. Lastly, applications for the instrument are discussed as well as some opportunities to improve it.